The language of hoofbeats - Hyde, Catherine Ryan (Lake Union Publishing, 2014)
New to a small town, Jackie and Paula envision a quiet life for their kids: a young adopted son and two teenage foster children, including the troubled Star. However, they quickly butt heads with their neighbor, Clementine, who disapproves of their lifestyle and is incensed when Star befriends her spirited horse, Comet. Haunted by past tragedy and unable to properly care for Comet, Clem nevertheless resents the bond Star soon shares with the horse. When Star disappears with Comet, the neighbors are thrown together--far too close together. But as the search for the pair wears on, both families must learn to put aside their animosity and confront the choices they've made and the scars they carry.